Legal and Institutional Determinants of Medical Solid Waste Management in Indonesia’s First-Level Health Facilities - Musdaleni Musdaleni (Jurnal Pembaharuan Hukum, 2026)
The management of medical solid waste in first-level healthcare facilities is a critical component of public health and environmental protection in Indonesia. This study examines the adequacy of the regulatory framework, the implementation of waste management practices, and strategies for improving compliance in primary healthcare settings. Using a normative juridical and policy-oriented approach, the research analyzes key legal instruments governing medical solid waste, including environmental, health, and waste management regulations. The findings indicate that Indonesia has established a comprehensive legal framework that clearly regulates waste segregation, storage, transportation, treatment, and disposal. However, empirical evidence from prior studies shows that implementation at the facility level remains inconsistent. Limited infrastructure, financial constraints, inadequate human resource capacity, and uneven regulatory enforcement hinder effective compliance, particularly in rural and resource-constrained areas. Many facilities depend on third-party waste providers, weakening accountability for proper segregation at the source. The study highlights the need for integrated strategies, including stronger regulation, capacity building, infrastructure investment, and better coordination between health and environmental authorities. The study concludes that aligning regulatory standards with institutional and operational capacities is crucial for achieving safe and sustainable medical solid waste management in first-level healthcare facilities in Indonesia.